EFEKTIVITAS PELAYANAN SURAT KETERANGAN CATATAN KEPOLISIAN (SKCK) DI POLRESTA SURAKARTA - Sri Riris Sugiyarti, Rizky Retnani Ningsih, Aris Tri Haryanto & (Transformasi, 2017)
This research was conducted to describing the service effectiveness of police clearancecertificate or SKCK at Sat Intelkam in Polresta Surakarta. The techniques used in this researchnamely, interview, observation, documentation. The informant is determined using a purposivesampling technique by choosing which is considered to know the problems in this research andaccidental sampling to select anyone that found while taking service of SKCK. As of indicatorsused to assesss the effectiveness of these services is a factor of resources, funds andinfrastructure, the amount and quality, the time limit, and ordinances. The results of thisresearch, indicate that the services of police clearance certificate at the Polresta Surakarta isalready effective.Key words : effectiveness, public service